HOW DO SAUDI MANAGERS MANIPULATE EARNINGS MANAGEMNT : PERSPECTIVE APPROACH FROM SAUDI LISTED COMANIES - الغامدي، سالم بن علي (جامعة بورسعيد - كلية التجارة, 2013)
The aim of this study is to investigate the techniques of aggressive earnings management in less developed economies using Saudi listed companies. While numerous earnings management studies exist in the literature, there are few empirical earnings management technique studies. The continuous failure of some Saudi listed firms, even since the introduction of the recent monitoring regulations, raises the necessity to investigate managers’ behaviour and earnings management practices through both qualitative and quantitative research approaches. The findings reveal that the four main techniques practised by Saudi managers to manipulate earnings are: manipulation of the provision of inventory; manipulation of the amount of receivable accounts; manipulation of the amount of depreciation accounts; manipulation of amount of expenses; manipulation of sales of assets; manipulation of internal transactions; and capitalising rather than expensing expenditure. These findings could be fruitful for external auditors, regulators and legislators in their attempts to reinforce the quality of monitoring mechanisms and enhance the integrity of financial reporting.
Keywords: المدراء السعوديون -- إدارة الأرباح -- الشركات -- سوق الأوراق المالية -- السعودية